2014
DOI: 10.1162/jocn_a_00665
|View full text |Cite
|
Sign up to set email alerts
|

Age-related Differences in the Neural Bases of Phonological and Semantic Processes

Abstract: Changes in language functions during normal aging are greater for phonological compared to semantic processes. To investigate the behavioral and neural basis for these age-related differences, we used functional magnetic resonance imaging (fMRI) to examine younger and older adults who made semantic and phonological decisions about pictures. The behavioral performance of older adults was less accurate and less efficient than younger adults’ in the phonological task, but did not differ in the semantic task. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 83 publications
3
40
3
Order By: Relevance
“…Semantic processes are well preserved in older adulthood, which may be surprising given the known gray and white matter reductions as a function of age. By contrast, elderly speakers do show marked difficulties with phonological retrieval, evidenced in more slips of the tongue [28]. This asymmetric pattern between phonological and semantic processes thus suggests that the two are dissociable.…”
Section: The Changing Brains Of L1 Attriters: What We Know From Previmentioning
confidence: 83%
See 1 more Smart Citation
“…Semantic processes are well preserved in older adulthood, which may be surprising given the known gray and white matter reductions as a function of age. By contrast, elderly speakers do show marked difficulties with phonological retrieval, evidenced in more slips of the tongue [28]. This asymmetric pattern between phonological and semantic processes thus suggests that the two are dissociable.…”
Section: The Changing Brains Of L1 Attriters: What We Know From Previmentioning
confidence: 83%
“…Given that the lexicon is the most and earliest affected domain in L1 attrition, this would be the best candidate, especially as this domain allows for the introduction of various levels of complexity, informed by previous findings. Most importantly, the dissociation between phonological and semantic learning and memory consolidation that has been found in past behavioral investigations [12] as well as in past fMRI work (albeit in the field of language and cognitive aging in monolinguals; [28]) can reveal if the same (lexical) domain is further subdivided (in phonology and semantic components) regarding the timeframe in which functional and/or anatomical changes in the brains of L1 attriters manifest themselves. Additionally, it allows for a controlled introduction of effects that have been found to influence bilingual processing in the past: cognate versus non-cognate status of words and frequency effects may all impact on a word's retention and attrition.…”
Section: The Changing Brains Of L1 Attriters: What We Need To Learn Fmentioning
confidence: 90%
“…Additionally, it could be argued that older individuals may have richer semantic representations, due to experience, as vocabulary scores increase with age (Diaz et al, 2014). If this holds, Catalan would have obtained lower imageability scores Hungarian, Greek, and Swedish.…”
Section: Mean Age Of Participantsmentioning
confidence: 99%
“…Instead, activity in this region has previously been observed in semantic-based tasks although its precise function in language processing is not yet well understood. Thus the finding of increased activity for concrete words in the young adults could potentially reflect processes involved with the retrieval of semantic knowledge (Binder et al, 2009;Diaz et al, 2014;Peelle, Troiani, Wingfield, & Grossman, 2010), which is greater for concrete concepts due to their richer set of conceptual features.…”
Section: Discussionmentioning
confidence: 98%
“…This recruitment by the older adults of a mechanism not used by the young group for abstract and pseudoword processing, accompanied by a preserved performance suggests an element of agerelated compensatory upregulation. Studies investigating differences between semantic and phonological processes and IFG activity have shown that different linguistic processing components can be differentially affected in ageing (Diaz, Johnson, Burke, & Madden, 2014;Geva et al, 2012;Meinzer et al, 2012;Meinzer, Wilser, et al, 2009;Shafto et al, 2012). Previous studies investigating concreteness have shown involvement of left inferior frontal regions when abstract words are directly contrasted with concrete words Fiebach & Friederici, 2004;Mellet et al, 1998;Noppeney & Price, 2004;Perani et al, 1999;Wise et al, 2000) and this may represent strategic retrieval of semantic knowledge (Fliessbach et al, 2006).…”
Section: Discussionmentioning
confidence: 99%